2023
DOI: 10.3390/ma16062360
|View full text |Cite
|
Sign up to set email alerts
|

Compressive Strength of Corrugated Paperboard Packages with Low and High Cutout Rates: Numerical Modelling and Experimental Validation

Abstract: The finite element method is a widely used numerical method to analyze structures in virtual space. This method can be used in the packaging industry to determine the mechanical properties of corrugated boxes. This study aims to create and validate a numerical model to predict the compression force of corrugated cardboard boxes by considering the influence of different cutout configurations of sidewalls. The types of investigated boxes are the following: the width and height of the boxes are 300 mm in each cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…In the study, the static analysis of the box compression, as shown in Figure 3A, replicated the laboratory test conditions, which was similar to [3,16,17]. In the finite element method (FEM) analysis, only the load-bearing walls of the packaging were modeled (Figure 4).…”
Section: Numerical Modeling Of the Resistance Of The Cardboard Packag...mentioning
confidence: 97%
See 1 more Smart Citation
“…In the study, the static analysis of the box compression, as shown in Figure 3A, replicated the laboratory test conditions, which was similar to [3,16,17]. In the finite element method (FEM) analysis, only the load-bearing walls of the packaging were modeled (Figure 4).…”
Section: Numerical Modeling Of the Resistance Of The Cardboard Packag...mentioning
confidence: 97%
“…The finite element method (FEM) is one of the most commonly used numerical methods for the mechanical analysis of structures [6,7]. The effectiveness of this method is confirmed by many scientific works and industrial implementations, including in the cardboard packaging industry [8][9][10][11][12][13][14][15][16]. The finite element method requires the use of detailed/accurate packaging geometry in order to obtain reliable calculation results.…”
Section: Introductionmentioning
confidence: 99%